Gardens of Grief: Lucy Hutchinson's "Elegies, " the Garden of Gethsemane, and Formal Uses of Betrayal. (2nd July 2016) - Lonich Ryan, Elise
Abstract : Lucy Hutchinson's "Elegies, " which were written in the late seventeenth century, mourn the loss of the poet's husband, Colonel John Hutchinson, and the loss of a republican form of government in the face of the Restoration. The garden landscapes in the poems that invoke Hutchinson's estate at Owthorpe are typically read as a figure for a lost Eden. I argue for a different biblical garden, however, the Garden of Gethsemane. Examining the poems' language of betrayal and grief alongside seventeenth-century exegesis on the Gethsemane episode, I show the correspondence between garden spaces, affect, and sympathetic textual and personal engagement. Using the psychoanalytic concept of conveyance, particularly in its gendered articulation in Julia Kristeva's Black Sun, I yoke exegesis to poetry in order to argue that mediating environments are capable of producing both subjects and affective experiences. Moreover, these formal products are contingent, depending on a continuous betrayal of the original lost object.